Green Marketing: The Disclosure of Sharia Values Through the Internalization of Service Marketing Mix Practices - Asnawi, Nur; Dwi Setyaningsih, Nina (International Journal of Engineering and Technology, 2019)
This study is aimed at determining the acculturation or internalization of sharia values occurring in Bank Muamalat Indonesia (BMI) and their implications upon the marketing strategy in the bank. This research is conducted using qualitative approach, revealing deeply about the cultural values of sharia in Bank Muamalat Indonesia. Depth interview with key informants and direct observation of the object, the obtained findings: 1) the corporate values of Sharia in BMI is known as Celestial Management Model, 2) the application of Interactive Marketing Strategy consists of internal, external and interactive marketing based on the values of sharia.Â Â